A mutation in autosomal dominant myotonia congenita affects pore properties of the muscle chloride channel - Fahlke, Christoph (The National Academy of Sciences of the USA, 1997)
Autosomal dominant myotonia congenita is an inherited disorder of skeletal muscle caused by mutations in a voltage-gated Cl(−) channel gene (CLCN1, 7q35). Here, we report that a mutation predicting the substitution of Gly 230 by glutamic acid (G230E) between segments D3 and D4 dramatically alters the pore properties of a recombinant human muscle Cl(−) channel (hClC-1) expressed in a mammalian cell line (tsA201). The G230E mutation causes substantial changes in anion and cation selectivity as well as a fundamental change in rectification of the current–voltage relationship. Whereas wild-type channels are characterized by pronounced inward rectification and a Cl > thiocyanate > Br > NO(3) > I > CH(3)SO(3) selectivity, G230E exhibits outward rectification at positive potentials and a thiocyanate > NO(3) > I > Br > Cl > CH(3)SO(3) selectivity. Furthermore, the cation-to-anion permeability ratio of the mutant is much greater than that of the wild-type channel. Voltage-dependent blocks by intracellular and extracellular iodide help to distinguish two distinct ion binding sites within the hClC-1 conduction pathway. Both binding sites are preserved in the mutant but have decreased affinities for iodide. These findings suggest that Gly 230 is critical for normal ion conductance in hClC-1 and that this residue resides within the channel pore.